Tantas águas, quantas histórias, diferentes narrativas ”“ o São Francisco dos viajantes - Brasil, Vanessa Maria (T.E.X.T.O.S DE H.I.S.T.Ó.R.I.A. Revista do Programa de Pós-graduação em História da UnB., 2010)
In the following article we are going to study the São Francisco river from the perspective found on the reports of four foreign travelers from the 1800’s. The literature of travel and exploration constitutes an inexhaustible source of information about this river, in both technical, literary and historiografical way. In several occasions this data, even the most relevant one, are supplied to us in a non-systematic and disorganized way, similar to the water of different riverbeds when it decides to meet. To make it translucent, both the article and the São Francisco, we shall take the work of different european naturalists as an imp ortant reference to the knowledge of environmental and natural history of Brazil. The contribution given by intellectuals that transit between History and Literature are also indispensable for this text.